2014
DOI: 10.4236/ojpsych.2014.43027
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Aspects of Infectious Diseases

Abstract: Psychiatric symptoms can be associated with several systemic and central nervous system infections and they can be the initial presenting symptoms, occurring in the absence of neurological symptoms in some disorders as in some cases of viral encephalitis. They could also be part of the clinical picture in other cases such as psychosis or mood symptoms secondary to brucellosis or toxoplasmosis. Late-onset neuropsychiatric complications may also occur several years following the infection such as in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…If the psychiatric symptoms can be explained pathologically by an underlying disease process, the diagnosis is most likely to be a psychiatric disorder due to a medical condition, rather than primary/functional psychiatric illness. So, itis important to differentiate psychiatric symptoms directly related to organic causes from those coincidentally occurring in a patient suffering from a primary psychiatric disorder [14].…”
Section: Discussionmentioning
confidence: 99%
“…If the psychiatric symptoms can be explained pathologically by an underlying disease process, the diagnosis is most likely to be a psychiatric disorder due to a medical condition, rather than primary/functional psychiatric illness. So, itis important to differentiate psychiatric symptoms directly related to organic causes from those coincidentally occurring in a patient suffering from a primary psychiatric disorder [14].…”
Section: Discussionmentioning
confidence: 99%
“…The course of HIV infection depends on various factors including the host, viral strain, treatment received and other environmental factors (1,2) . Treatment of concomitant infections is of primary importance in the delaying of disease progression in HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that simultaneous infections occurring with HIV infection can affect the HIV disease adversely (1) . Examples of these infections include tuberculosis, viral infections such as cytomegalovirus, and parasitic infections such as toxoplasmosis (2) . Lymphatic filariasis is caused by a thin thread-like parasite that lives in the lymph vessels, causing a significant disability in infected people.…”
Section: Introductionmentioning
confidence: 99%
“…One year after hospital treatment in 70 of the same patients, 16% had memory disorders, 9% showed signs of aggressiveness, and 8% suffered from aphasia, 8% from visual hallucinations, and 7% from auditory hallucinations [ 41 ]. Brucellosis, typhoid fever, Lyme disease, Leptospirosis, and Whipple's disease are all examples of inflammatory diseases caused by infection that can be accompanied by psychiatric symptoms ranging from depression, mania, personality trait, and behavioral changes to manifest psychosis [ 42 ]. Regarding inflammation during healing after trauma, a survey of 722 outpatients after brain injury with an average of 10 days' unconsciousness after injury found a rate of DSM-IV valuable diagnosis of depression in 42% of patients [ 43 ].…”
Section: Relationship Between Inflammation and Mental Illnessmentioning
confidence: 99%